MEASURING THE TECHNICAL EFFICIENCY OF POTATO PRDUCTION AND ITS DETERMINATS IN IRAQ (BAGHDAD PROVINCE AS CASE STUDY). - & et al., Al-Hachami (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study aimed to estimate the stochastic frontier production function and the inefficiency function and technical efficiency of potato production by using cross-section data collected from 173 potato farms that were randomly selected in Baghdad province/ Yusifiyah for production season 2016. The results showed that 90.6% of inefficiency in production was due to technical inefficiency. Also, there was a significant relationship between the variables of inefficiency function and the inefficiency of farms. The values of the parameters of the stochastic frontier production function were positive and significant for both human work hours and the amount of seeds. However, the parameter of DAP fertilizer was negative and significant. The estimation of the technical inefficiency function showed that its parameters were significant for both the local seed provider and the agricultural season (fall), while the parameters experience in growing potatoes and the number of irrigations were significant and their impact was negative on the inefficiency. The results also showed that the technical efficiency of the study sample (50%) on average. The researchers recommended the necessity of providing imported seed tubers for the increased productivity in dunum to achieve technical efficiency.